Handbook of Social Movements Across Disciplines - Klandermans, Bert.; Roggeband, Conny; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Researchers and students from divergent academic disciplines share an interest in the study of social movements and collective action. Through a variety of disciplinary approaches and techniques, researchers seek to understand the emergence and development of collective action. In the last few decades, the field of social-movements-studies has proliferated enormously, covering a wide array of movements, issues and places. With this growth, social movement scholars have criticized the traditional vision of collective mobilization as the results of irrational behavior and have instead developed a range of new approaches. The expansion of the field has also led to increased theoretical debates and attempts to synthesize the different perspectives. With this in mind, this seminal volume revisits the disciplinary roots of social movement studies. Each discipline raises its own questions and approaches the subject from a different perspective. This volume combines these divergent perspectives into one cohesive, comprehensive work.
Structural Approaches in the Sociology of Social Movements -- Cultural Approaches in the Sociology of Social Movements -- Assessing the Politics of Protest Political Science and the Study of Social Movements -- Individuals in Movements -- Anthropology and the Study of Social Movements -- Historians and the Study of Protest*.
Keywords: Sociology; Social Sciences, general; Sociology